Effect of Leadership on the Employee Satisfaction and Attitude in the Automobile Distributing Firms - Timilsina, Sambed (Journal of Vishwa Adarsha College, 2024)
Leadership in the contemporary world is about leading the ever-changing business environment with sheer resilience, courage, honesty, and integrity. This paper examines the relationship between leadership style, role, and functioning of the organization effectively and scientifically as well as explores the relationship between leadership style and employees' satisfaction with their job. The research paper is based on primary data based on a survey of managerial-level and middle-level employees of automobile industries through a structured questionnaire. All the collected data were analyzed using descriptive and inferential statistics with the assistance of SPSS version 20. Results revealed that the leadership style has a significant influence on the smooth functioning of the business firms as it affects the employees’ satisfaction. Leaders demonstrate a democratic leadership style that makes workers happy at work and fosters favorable attitudes toward both the organization and their work.